Nutritive value of Tifton 85 hay ammoniated with urea - Almeida, João Carlos de Carvalho; Morais, Leonardo Fiusa de; Moreira, Thaís Gláucia Bueno; Abreu, João Batista Rodrigues de; Morenz, Mirton José Frota (Acta Scientiarum. Animal Sciences, 2018)
The effect of ammonization was evaluated with urea at doses of 1, 2, 3 and 4%, on the basis of dry matter (DM) on Tifton 85 hay harvested at an advanced stage of development in the periods of 30 and 45 days, through analysis of dry matter, ash, ether extract (EE), neutral (NDF) and acid (ADF) detergent fiber, NDF corrected for ash and protein (NDFap), cellulose, lignin, crude protein (CP), acid detergent insoluble nitrogen (ADIN), fractionation of carbohydrates and in vitro gas production (Parameters: Vf1, k1, Vf2, k2 and L). The variables DM, EE, NDF, ADF, lignin, cellulose, NDFap, fraction A + B1, fraction B2 and C of carbohydrates, and the Vf1 and Vf2 parameters were influenced by treatments (p < 0.05). While DM, NDF, NDFap, fraction A + B1, C, CP and Vf2 showed linear effects according to the dose, NIDA and hemicellulose presented quadratic effects. Vf1 and Vf2 were also influenced by the treatment period. The ammonization with 2.7% urea on the basis of DM promotes improvement of Tifton 85 hay treated for 45 days, observed after derivation of the regression equation and evaluation of the nutritional and kinetic degradation in vitro.